2013
DOI: 10.1016/j.jmb.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule FRET Reveals the Native-State Dynamics of the IκBα Ankyrin Repeat Domain

Abstract: Previous single-molecule fluorescence resonance energy transfer (smFRET) studies in which the second and sixth ankyrin repeats (ARs) of IκBα were labeled with FRET pairs showed slow fluctuations as if the IκBα AR domain was unfolding in its native state. To systematically probe where these slow dynamic fluctuations occur, we now present data from smFRET studies wherein FRET labels were placed at ARs 1 and 4 (mutant named AR 1–4), at ARs 2 and 5 (AR 2–5), and at ARs 3 and 6 (AR 3–6). The results presented here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
(82 reference statements)
1
27
0
Order By: Relevance
“…For example, for donor/acceptor probes located at AR 1 and AR 4 and at 298 K, a broad peak centered at high FRET values is seen (blue in Figure 3D) indicating that the protein is well-folded though with fluctuations from sampling partially-structured conformations (I 2 ; Figure 3A). At 310 K, the predicted mean FRET is lower and broader as a result to populating more disordered regions as represented by increasing distances for lower values of RC, exactly as observed in experiments [15]. Though there is a correlation between experiments and simulations on the mean FRET values of the first and second peak (Figure 3H) we do not capture the experimental amplitude, i.e.…”
Section: Resultsmentioning
confidence: 61%
“…For example, for donor/acceptor probes located at AR 1 and AR 4 and at 298 K, a broad peak centered at high FRET values is seen (blue in Figure 3D) indicating that the protein is well-folded though with fluctuations from sampling partially-structured conformations (I 2 ; Figure 3A). At 310 K, the predicted mean FRET is lower and broader as a result to populating more disordered regions as represented by increasing distances for lower values of RC, exactly as observed in experiments [15]. Though there is a correlation between experiments and simulations on the mean FRET values of the first and second peak (Figure 3H) we do not capture the experimental amplitude, i.e.…”
Section: Resultsmentioning
confidence: 61%
“…By placing the donor and acceptor fluorophores at various positions, Lamboy et al (14) were able to obtain information about the flexibility of each repeat with respect to others, and the results revealed that AR1 fluctuates in both the free and NFkB-bound states, whereas AR2 and AR4 never appear to fluctuate. Fluctuations were observed when FRET pairs were placed at AR3 and AR6, but since fluctuations were also observed when the FRET pairs were placed at AR2 and AR6, these fluctuations were attributed to fluctuation of AR6 (14).…”
Section: Introductionmentioning
confidence: 99%
“…A later smFRET study by the same authors showed that the AR 6 domain was more prone to disorder than the AR 5 domain. Thus, while the AR 5 domain did not show disorder at room temperature (requiring an increase to 37 °C to show disorder), the AR 6 domain demonstrated disordered even at room temperature 29 .…”
Section: Structural Features and Dynamics Of Monomeric Idpsmentioning
confidence: 94%